THE IMPORTANCE OF ERROR CORRECTION IN FOREIGN LANGUAGE LEARNING: THE IMPORTANCE OF ERROR CORRECTION IN FOREIGN LANGUAGE LEARNING - Djumanazarova, Khalima (Журнал иностранных языков и лингвистики, 2025)
There is nobody who is able to learn a foreign language without making errors during the phases of language acquisition. That is why this field of study deserves a great deal of linguists’ attention. Teachers are an essential part of this learning process, as they are usually those who help students correct their errors and avoid them in the future. However, in time students also become active participants in their own learning process